Improving Student Quality Through Extracurricular Programs: Case Study on Ma’had IAIN Padangsidimpuan - Diyah Hoiriyah; Tatta Herawati Daulae (Institut Agama Islam Negeri Padangsidimpuan, 2022)
This research was motivated by the increasing learning outcomes obtained by some students after joining the ma'had program. Especially in semester III, there were many students who took lectures to semester IV, due to the GPA (Grade Point Average) they obtained and also the participation of students in scientific forums both locally and nationally. The research problem formulations were what ma'had programs in improving the quality of students, how to do it and how the evaluation system was. This study aimed to determine ma'had programs in improving the quality of students, how to do it and the evaluation system. The purpose of this research was to broaden the knowledge about student coaching. The discussion of this research related to the theory of quality improvement, extracurricular programs and ma'had or boarding schools. The research used descriptive method, the number of respondents was 25 from ma'had coaches, the instrument used observation and interviews, while the analysis of data by compiling data editors, selecting data, describing data and drawing conclusions. The results of this study therewere six ma'had programs in improving the quality of students at IAIN Padangsidimpuan. The ways to do the program were arranging the daily, weekly schedule and doing the program. The evaluation system was carried out following odd and even semester examinations. The forms of the test were oral, written and practical. If it was related with improving the quality of students, there was clearly an increase in quality that classified as high, medium and low